Development of a water quality index to assess and classify water quality in the coastal waters of Hai Phong (Vietnam) - Le, Van Nam; Nguyen, Thi Mai Luu; Le, Xuan Sinh; Duong , Thanh Nghi; Pham, Thi Kha; Cao, Thi Thu Trang; Dang, Hoai Nhon; Nguyen, Van Bach; Nguyen, Thi Thu Ha; Dang Thi Kim Chi, Dang Thi Kim Chi (Vietnam Journal of Marine Science and Technology, 2025)
The method of developing the water quality index (WQI) to evaluate and classify the water quality of the coastal waters of Hai Phong (2019) includes the following steps: selecting parameters, calculating sub - indices, determining weights, calculating the WQI, building a classification scale, and testing the formula. The water quality of Hai Phong’s coastal waters varied widely, ranging from very poor to excellent. The water quality of Hai Phong’s coastal waters tended to improve from the river mouths to the sea. In the rainy season, the areas with very poor and poor water quality tended to expand, while the areas with medium and good water quality tended to shrink compared to the dry season. The area of excellent water quality showed little seasonal variation. During high tide, water quality was typically better than during low tide. The water quality at the Bach Dang, Lach Tray, Van Uc, and Thai Binh estuaries was very poor during low tide (WQI from 19 to 22) and poor during high tide (WQI from 43 to 45) in both the dry and rainy seasons. The South - Southwest area of the Hai Phong coastal estuary generally had worse water quality compared to the North and Northeast areas. The Ben Beo area (the main port of Cat Ba Island, where most of the island’s large and small boats gathered) had medium water quality (WQI from 62 to 73). This area was at a higher risk of environmental pollution compared to other areas in the Cat Ba Island sea. The outside area had water quality ranging from good to excellent.